Can routine hemogram parameters be used as inflammatory biomarker in chronic obstructive pulmonary disease exacerbations? (Annals of Medical Research, 2021)
Aim: Confirming the diagnosis and identifying the etiology are critical for the management of chronic obstructive pulmonary disease(COPD) exacerbation. There is limited use of hemogram and C-reactive protein (CRP) in distinguishing infectious or non-infectious in exacerbations. However, procalcitonin is more precious in making this distinction, although it is less accessible and more expensive. The aim of this study was to investigate the association between procalcitonin, CRP, hemogram parameters and ratios, and the efficacy of new hematological ratios in differential diagnosis in subjects with COPD exacerbation.Materials and Methods: Subjects admitted to our outpatient clinic with the diagnosis of COPD were retrospectively analyzed and divided into 2 groups: those with acute exacerbation (n=52) and those are stable (n=64). Neutrophil-lymphocyte ratio (NLR), monocyte-lymphocyte ratio (MLR) and platelet-lymphocyte ratio (PLR) were calculated for both groups. Subjects were grouped according to NLR cut-off point determined by the ROC curve (NLR